2018
DOI: 10.1007/s11748-018-1022-y
|View full text |Cite|
|
Sign up to set email alerts
|

Risk assessments for broncho-pleural fistula and respiratory failure after lung cancer surgery by National Clinical Database Japan

Abstract: Background Broncho-pleural fistula (BPF) and respiratory failure (RF) are life-threatening complications after lung cancer surgery and can result in long-term hospitalization and decreased quality of life. Risk assessments for BPF and RF in addition to mortality and major morbidities are indispensable in surgical decision-making and perioperative care. Methods The characteristics and operative data of 80,095 patients who had undergone lung cancer surgery were derived from the 2014 and 2015 National Clinical Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…According to data from a national clinical database in Japan, interstitial pneumonia, central nerve system disorder, autoimmune disease, and smoking habit are reported risk factors for BPF. 15) In this study, the only risk factor for BPF identified by multivariate analysis in patients undergoing lobectomy was diabetes (HbA1c ≥8.0). Moreover, although ASO was not identified by multivariate analysis, it is also a possible risk factor.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…According to data from a national clinical database in Japan, interstitial pneumonia, central nerve system disorder, autoimmune disease, and smoking habit are reported risk factors for BPF. 15) In this study, the only risk factor for BPF identified by multivariate analysis in patients undergoing lobectomy was diabetes (HbA1c ≥8.0). Moreover, although ASO was not identified by multivariate analysis, it is also a possible risk factor.…”
Section: Discussionmentioning
confidence: 65%
“…Endo et al reported risk factors for BPF drawn from a national clinical database in Japan. 15) Regarding surgical procedure, right pneumonectomy was a stronger risk factor (odds ratio 11.1) than bronchoplasty with segmentectomy or lobectomy (odds ratio 5.4). Admittedly, advanced techniques are required for plastic surgery.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of 798 patients, BPFs developed in 96 (12%), of whom 42 (44%) died within 90 days of operation. In recent large surveys, the frequency of post-operative BPF ranged from 0.3% to 0.9% (2)(3)(4). In a French national database including information on 34,000 patients treated via pulmonary resection, the incidence of post-operative BPF was 0.9% (318 patients), and the associated mortality was 22% (70 patients) (2).…”
mentioning
confidence: 99%
“…In a French national database including information on 34,000 patients treated via pulmonary resection, the incidence of post-operative BPF was 0.9% (318 patients), and the associated mortality was 22% (70 patients) (2). In a Japanese national database including information on 78,594 patients who underwent lung cancer resection, the incidence of post-operative BPF was reportedly only 0.3% (259 patients), but mortality within 30 days of surgery was 19% (4). In patients with BPFs, infectious pleural effusions in the thoracic cavity flow into the healthy lung through the fistulae, triggering intractable infectious conditions including pneumonia and sepsis.…”
mentioning
confidence: 99%